Mind the Gap: Reach and Mechanical Diversity of Searcher Shoots in Climbing Plants - Hattermann, Tom; Petit-Bagnard, Laureline; Heinz, Christine; Heuret, Patrick; Rowe, Nick P. (Frontiers in Forests and Global Change, 2022)
Climbing plants need to reach supports and position their leaves for light capture. Vines and lianas develop a large diversity of self-supporting shoots among diverse species and different kinds of attachment. A searcher’s reach is a crucial trait for colonizing supports in complex 3-dimensional spaces. We explore the reach capacity and diversity of searcher shoots among representative temperate and tropical climbing plants. We investigate what is the overall range of variation between short- and long-reach searchers; what are the principal kinds of mechanical and anatomical organization underlying reach capacities and across diverse species; how are different searcher architectures linked to different climbing strategies such stem twining, tendril climbing, root climbing and branch-angle-hook climbing. We investigated searcher reach, mechanical and anatomical organization (stem rigidity stiffness, stem and tissue geometry) in 29 climbing plant species from temperate and tropical habitats. Searchers show a wide range of maximal reach per species from 0.1 to 2.5 m. Flexural rigidity (EI) at the base of searchers increased with reach length; overall this increase was proportional although some longest-reaching shoots develop proportionally thinner searcher bases with higher structural Young’s modulus (Estr) than shorter-reach shoots. Bases of short-reach searchers rely more on primary tissues compared to long-reach shoots, which rely more on wood production. We identified different mechanical architectures for a given reach capacity across all species, which are linked to different kinds of attachment mechanism, support foraging and possibly leaf display. Plants attaching by twining of the main searcher shoot stem, showed a wide range of reach capacity, developing lighter, more slender, less rigid, but generally relatively stiff (higher Estr) shoots compared with tendril climbers and branch-angle-hook climbers. Differences in mechanical architecture of searcher shoots in climbing plants are informative for understanding how diverse climbing plant species explore and colonize different kinds of three-dimensional spaces, a key feature that distinguishes different habitat preferences. Finally, we discuss how such knowledge is not only important for the functional biology and ecology of climbing plants but is also of interest for developing new technologies in soft robotics that mimic climbing plants that can navigate through unstructured environments.